Vitamin D Deficiency among the Children: A Silent Epidemic in a Selected Rural Area of Bangladesh (Journal of Enam Medical College, 2021)
Background: Vitamin D deficiency is widespread among the children worldwide. Most of the third world countries have the high prevalence of vitamin D deficiency, especially among the children. Unfortunately very less research work has been conducted on this subject and Bangladesh is no exception to this. Vitamin D deficiency among the Bangladeshi children has not been investigated at a level that could bring the phenomenon to the fore of the concerned stakeholders and policy makers.Objective: To assess the prevalence of vitamin D deficiency among children in Kaliakoir Upazila, Gazipur District, Bangladesh.Materials and Methods: A cross-sectional study was conducted in children aged 0 month to